THE EFFECTIVENESS OF USING WORDWALL MEDIA IN INCREASING STUDENTS’ INTEREST IN ISLAMIC CULTURAL HISTORY - Haris, Abdul; Permadi, Rudi; Azijah, Sarah Noor; Latifah, Lala (Universitas Pendidikan Indonesia, 2025)
This study aims to determine whether the use of Wordwall as a learning media is effective in increasing students' interest in learning Islamic Cultural History class XI MAN 2 Tasikmalaya City. This research is non-experimental quantitative research with survey research method. The population in this study was grade XI MAN 2 Kota Tasikmalaya consisting 55 students. The instrument used is a questionnaire. Data collection techniques used are observation, questionnaires, and documentation. The analysis technique uses product moment correlation at a significant level of 5%. The results showed that the learning process was more interactive and fun. From the results of simple linear regression analysis, it is known that the effect of Wordwall learning media (independent variable) on learning interest (dependent variable) is 34.7% and the remaining 0.653% is influenced by other dependent variables. So it can be drawn that the null hypothesis (H0) is rejected and (Ha) is accepted. It can be concluded that the use of Wordwall media as a learning media is effective in increasing students' interest in learning subject of Islamic Cultural History Class XI MAN 2 Kota Tasikmalaya.